التنظيم الدستوري والقانوني للحق في التعليم - طالب مصدق عادل; حسين مرتضى (Journal of Legal Sciences, 2017)
The right of education is regarded renewable human rights, which is almost the different constitutions and laws organized the matter relate to it, the reason of special arrangement is the right measure of urbanization and the progress of society and any state. In this sense, our research was to shed light on the constitutional and legal regulation of the right to education in Iraq compared with the other countries of the Arab republic of Egypt in order to put controls govern this right and how to enjoy it.